TANGGUNG JAWAB HUKUM PELAKU USAHA TERHADAP TRANSAKSI PEMBELIAN BARANG ADANYA CACAT TERSEMBUNYI OLEH KONSUMEN (Studi Putusan Nomor Perkara 77/PDT/2018/PT.DKI) - Eveline Wijaya; Jeane Neltje Saly (Jurnal Hukum Adigama, 2021)
Transportation is a very important means for human life. There is a consumer buying interest in vehicles to meet their needs a day, which makes it easier tomovefromoneplacetoanother. In fact, the sellers in marketing or selling their products provide information in such a way as if the car sold has met the standards without any hidden defects or other shortcomings, thus encouraging consumers to buy based on trust alone. In this paper there are problems that will be discussed, namely how the legal responsibility of businesses against the existenceofhiddendefectsinthe goods sold and how dispute resolution steps that can be taken by consumers if harmed by the purchase of hidden defective goods. Legal settlements taken to resolve cases of hidden defects as a result of legal relationships between businesses and consumers as legal subjects of the parties to trade agreements in which the appropriate legal mechanism is through arbitration channels. The author hopes that businesses are obliged to refund the price of goods purchased by consumers and the appropriate legal mechanism is through arbitration because the settlement path the parties can determine for themselves the place of legal settlement and who will be the arbitrator and what solutions each party wants.